Pengaruh Perambahan Hutan Terhadap Debit Mata Air Tubaki dalam Kawasan Hutan Suaka Margasatwa Kateri 254 Desa Wehali Kecamatan Malaka Tengah Kabupaten Malaka - Magdalena Gabriela Nahak; Ludji Michael Riwu Kaho; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Kateri Wildlife Sanctuary is one of the conservation areas in East Nusa Tenggara that has been experiencing forest destruction and habitat degradation, caused by forest encroachment by irresponsible parties. The impact of forest destruction has implications for various environmental components, ecosystems, and habitats. The loss of forest vegetation will disrupt the local microclimate and cause an increase in temperature, resulting in high evaporation, a decrease in groundwater levels, and a reduction in surface water. Areas with hilly topography and steep slopes have minimal ground cover by vegetation. In the rainy season, water is abundant, but in the dry season, there is a shortage of water. This study aims to determine how much influence encroachment has on Tubaki spring discharge using quantitative methods conducted from September to December 2022. The data collected with xxx methods The results of the study of Tubaki spring discharge tended to decrease due to forest encroachment that occurred in the area above Tubaki spring. Land cover of forest types experienced changes in cover from 1999 to 2022 tends to decrease. In 1999, forest land cover amounted to 37.52% and will reach 11.20% in 2022. The correlation coefficient between forest encroachment and spring discharge is in the strong category, and the current amount of spring discharge is 78.47% influenced by forest encroachment, while the other 21.53% is influenced by other factors that cannot be explained in this research method.